2014
DOI: 10.1044/2013_lshss-12-0104
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Receptive Vocabulary Growth in Young Spanish English–Speaking Children From Migrant Families

Abstract: ELLs from low socioeconomic backgrounds may be expected to perform lower in English compared with their monolingual English peers in kindergarten. Performance in Spanish at school entry may be useful in identifying children who require more intensive instructional support for English vocabulary growth. Findings substantiate the need for progress monitoring across the early school years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 34 publications
(57 reference statements)
2
32
0
1
Order By: Relevance
“…As stated previously, this issue has the potential to result in over-or underestimation of skills. Studies show that bilingual children's mean vocabulary scores on standardized assessments tend to be below those of monolingual children in both languages when each language (i.e., Spanish and English) is measured separately (Bialystok, Luk, Peets, & Yang, 2010;Hammer, Lawrence, & Miccio, 2008;Jackson, Schatschneider, & Leacox, 2014;Páez, Tabors, & López, 2007;Uccelli & Páez, 2007;Uchikoshi, 2006). Consequently, alternative measures have been proposed that take into account both languages of the bilingual child when appraising the lexicon.…”
Section: Bilingual Vocabulary Appraisalmentioning
confidence: 95%
“…As stated previously, this issue has the potential to result in over-or underestimation of skills. Studies show that bilingual children's mean vocabulary scores on standardized assessments tend to be below those of monolingual children in both languages when each language (i.e., Spanish and English) is measured separately (Bialystok, Luk, Peets, & Yang, 2010;Hammer, Lawrence, & Miccio, 2008;Jackson, Schatschneider, & Leacox, 2014;Páez, Tabors, & López, 2007;Uccelli & Páez, 2007;Uchikoshi, 2006). Consequently, alternative measures have been proposed that take into account both languages of the bilingual child when appraising the lexicon.…”
Section: Bilingual Vocabulary Appraisalmentioning
confidence: 95%
“…There are also "child" factors that have been shown to relate to vocabulary development. It has been frequently reported that girls outperform boys under 4 years of age (Harrison & McLeod, 2010;Reilly et al, 2009;Skeat et al, 2010;Zambrana, Pons, Eadie, & Ystrom, 2014) and girls and boys respond differently to known risks such as SES and parental input (Bornstein et al, 2004;Zambrana et al, 2014) whereas other studies have found no gender-based differences (Jackson, Schatschneider, & Leacox, 2014). Other child factors that have been found to be related to the acquisition of words are low birth weight (Leijon, Ingemansson, Nelson, Wadsby, & Samuelsson, 2016;Taylor et al, 2013), children's behaviour, and non-verbal cognitive skills (Beitchman et al, 2008;Law et al, 2012).…”
Section: Influences On Vocabulary Developmentmentioning
confidence: 99%
“…For example, a study by Jackson et al (2014) looked at receptive vocabulary attainment in Spanish-speaking ELLs from migrant families. Jackson et al recruited 64 ELL kindergartners from low SES migrant families and had participants complete standardized vocabulary tests every 6 months from kindergarten through second grade.…”
Section: Bilingual Language Ability and Sesmentioning
confidence: 99%
“…An additional variable within this trend is language diversity, given that there is a higher occurrence of poverty among minority language communities (Ryan, 2013). The poverty rate for Hispanic children is 30.4% (U.S. Department of Health and Human Services, 2014), and there is a disproportionate prevalence of childhood poverty among Latino and English language learners (ELLs; Jackson, Schatschneider, & Leacox, 2014). Children from these communities may demonstrate potentially confusable weaknesses in English due to mixed effects of low SES and bilingualism that are separate from brain-based language disorders.…”
mentioning
confidence: 99%